Aerogel modified inorganic base deep well tunnel heat insulation cooling coating and preparation method thereof
Patent Information
- Application Number
- CN202611133212.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-29
AI Technical Summary
由于水的导热能力明显高于静止空气,隔热层的含水量增加会造成有效导热能力升高,从而削弱其对围岩热量的阻隔作用
1、经界面调控后的SiO2气凝胶表面同时保留疏水基团和适量亲水性结合位点。疏水基团能够减少高湿环境中的水分进入气凝胶纳米孔道,避免孔内静止空气被水分取代;亲水性结合位点则改善气凝胶在无机浆体中的润湿和分散状态,降低浮粉、团聚及界面脱粘的可能性。稀疏界面层不会对气凝胶形成厚重包覆,因而能够较好地保留其纳米孔结构。气凝胶均匀分布于涂层后,其纳米孔可以限制孔内气体运动,并使围岩热量在涂层中的传递路径变得曲折,从而降低涂层中的气相传热和固相传热。
Smart Images

Figure CN122628583B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional coatings technology, specifically to an aerogel-modified inorganic-based thermal insulation and cooling coating for deep well tunnels and its preparation method. Background Technology
[0002] As mining depth increases, underground strata temperatures gradually rise, and the temperature of the surrounding rock in deep mine tunnels is typically higher than the air temperature inside. Given this temperature difference, heat stored within the surrounding rock is continuously conducted along the rock mass from the high-temperature areas to the tunnel walls. Once at the tunnel walls, the heat enters the working space through convection and radiation, making the surrounding rock a continuous heat source releasing heat into the tunnel. Deep mine tunnels are characterized by their considerable length, distance from the surface, and long ventilation paths. Fresh air, during its transport, comes into prolonged contact with the warmer surrounding rock walls, continuously absorbing the heat released by the rock, causing the air temperature to gradually rise along the ventilation direction. As tunnel excavation continues and the exposed area of the surrounding rock increases, the area where the surrounding rock participates in heat dissipation expands accordingly, increasing the amount of heat entering the tunnel space. When the heat released by the surrounding rock cannot be carried away in time, it accumulates within the tunnel, leading to a rise in the temperature of the working area. Deep mine tunnels also typically exhibit environmental characteristics such as high air humidity, damp walls, and localized water seepage. High humidity and water seepage increase heat and mass transfer near the tunnel walls and may cause the insulation layer on the walls to absorb water. Once the insulation layer absorbs water, the pores originally occupied by air may be partially filled with moisture. Since water has a significantly higher thermal conductivity than still air, the increased water content of the insulation layer will increase its effective thermal conductivity, thereby weakening its ability to block heat from the surrounding rock. Therefore, the tunnel wall insulation layer not only needs to have low initial thermal conductivity but also needs to maintain stable insulation performance under long-term high humidity or localized water seepage conditions.
[0003] To reduce the continuous heat transfer from the surrounding rock to the tunnel air, a continuous thermal insulation coating with sufficient coverage needs to be formed on the rock wall. This coating should be tightly bonded to the tunnel wall, providing continuous coverage over uneven, porous, or irregularly shaped areas to prevent concentrated heat transfer channels caused by gaps, holes, or seams. Simultaneously, the coating should have a low thermal conductivity, requiring heat to travel a longer and more tortuous path through it, thereby reducing the amount of heat transferred from the surrounding rock to the tunnel working space per unit time. Furthermore, the thermal insulation coating should possess water resistance stability to withstand the high humidity environment of deep wells. Under the long-term effects of humid air, wall moisture, and localized seepage, the coating should minimize the entry of moisture into its internal pores, maintaining its low thermal conductivity structure and continuous bonding with the tunnel wall. By forming a continuous, low-thermal-conductivity, and high-humidity-resistant thermal insulation coating on the tunnel wall, the rate of heat transfer from the interior of the surrounding rock to the wall and tunnel air can be slowed, reducing the continuous impact of surrounding rock heat dissipation on the working space temperature. Summary of the Invention
[0004] The purpose of this invention is to provide an aerogel-modified inorganic-based thermal insulation and cooling coating for deep well tunnels and its preparation method, so as to solve the technical problems mentioned in the background.
[0005] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing an aerogel-modified inorganic-based thermal insulation and cooling coating for deep well tunnels includes the following steps: S1. A partially hydrophobic SiO2 aerogel with both hydrophobic groups and reactive silanol groups on its surface is contacted with aminosilane and epoxysilane in an alcohol-water medium, so that the aminosilane and epoxysilane are hydrolyzed and condensed on the surface of the aerogel to obtain an organosiloxane interface layer modified SiO2 aerogel. S2. Hydrolyze and condense the hydrolyzable silicon source and the hydrolyzable zirconium source on the surface of the hollow glass microspheres, and then solidify them to form a SiO2-ZrO2 composite shell, thus obtaining composite shell modified hollow glass microspheres. S3. Premix expanded vermiculite with short-cut basalt fibers, and then mix it with inorganic powder containing sulfoaluminate cement, calcium sulfate, metakaolin, and wollastonite to obtain an inorganic skeleton premix. S4. The inorganic skeleton premix is mixed with water to form an inorganic slurry. Modified SiO2 aerogel and composite shell modified hollow glass microspheres are added to the inorganic slurry in sequence. After mixing evenly, the heat insulation and cooling coating is obtained.
[0006] Preferably, in step S1, the partially hydrophobic SiO2 aerogel is a SiO2 aerogel that has undergone incomplete methylation treatment with hexamethyldisilazane.
[0007] Preferably, in step S1, the aminosilane is 3-aminopropyltriethoxysilane, and the epoxysilane is 3-glycidoxypropyltrimethoxysilane. Based on 100 parts by weight of partially hydrophobic SiO2 aerogel, the amount of 3-aminopropyltriethoxysilane is 2.2 to 2.5 parts, and the amount of 3-glycidoxypropyltrimethoxysilane is 3.2 to 3.6 parts.
[0008] Preferably, in step S2, the D50 of the hollow glass microspheres is 25-55 μm; the hydrolyzable silicon source is tetraethyl orthosilicate; the hydrolyzable zirconium source is zirconium propoxide; and the zirconium propoxide is coordinated with acetylacetone.
[0009] Preferably, step S2 includes: Based on 100 parts by weight of hollow glass microspheres, 6-10 parts of tetraethyl orthosilicate were added to an alcohol-water medium and pre-hydrolyzed for 20-40 min at pH 3.5-4.0 and 20-30℃. 0.9 to 1.6 parts of zirconium propoxide based on the effective ingredient were premixed with acetylacetone to make the molar ratio of acetylacetone to zirconium (0.3 to 0.5):1, and then added to the pre-hydrolyzed tetraethyl orthosilicate solution. Add hollow glass microspheres and stir at 35–40°C for 1.5–2.5 h. Adjust the pH of the system to 7.2–7.8 and continue stirring for 0.5–1.5 h. Then filter, wash and dry.
[0010] Preferably, the dried hollow glass microspheres are heated to 280-320°C at a heating rate of 1-3°C / min and held at that temperature for 0.5-1.5 hours to solidify the SiO2-ZrO2 composite shell.
[0011] Preferably, the expanded vermiculite in step S3 has a particle size of 60-100 mesh and a bulk density of 80-150 kg / m³. 3 The chopped basalt fibers have a length of 2–4 mm and a diameter of 9–17 μm.
[0012] As a preferred option, an adjuvant is also added in step S3; The additives include polycarboxylate superplasticizer, hydroxypropyl methylcellulose water-retaining and thickening agent, and powder defoamer.
[0013] Preferably, the mass fraction ratio of the heat insulation and cooling coating components is as follows: The composition includes 32-40 parts of sulfoaluminate cement, 3-5 parts of calcium sulfate, 10-16 parts of metakaolin, 8-12 parts of modified SiO2 aerogel, 15-21 parts of composite shell modified hollow glass microspheres, 6-10 parts of expanded vermiculite, 0.4-0.8 parts of short-cut basalt fiber, 6-10 parts of acicular wollastonite, 0.3-0.6 parts of polycarboxylate superplasticizer, 0.15-0.25 parts of hydroxypropyl methylcellulose, and 0.2-0.4 parts of powder defoamer.
[0014] An aerogel-modified inorganic-based thermal insulation and cooling coating for deep well tunnels is prepared by the method described above.
[0015] Compared with the prior art, the beneficial effects of the present invention are: 1. The SiO2 aerogel surface, after interface modulation, retains both hydrophobic groups and a suitable amount of hydrophilic binding sites. The hydrophobic groups reduce the entry of moisture into the aerogel nanopores in high-humidity environments, preventing the replacement of stagnant air within the pores by moisture; the hydrophilic binding sites improve the wetting and dispersion of the aerogel in inorganic slurries, reducing the possibility of powder floating, agglomeration, and interface debonding. The sparse interface layer does not form a thick coating on the aerogel, thus better preserving its nanoporous structure. After the aerogel is uniformly distributed in the coating, its nanopores can restrict gas movement within the pores and make the heat transfer path of the surrounding rock in the coating more tortuous, thereby reducing gas-phase heat transfer and solid-phase heat transfer in the coating.
[0016] 2. The SiO2-ZrO2 composite shell protects the weak points on the surface of the hollow glass microspheres, improving their ability to withstand stirring, transport, and spraying. When the microsphere structure remains intact, its internal closed air cavity can continuously provide insulation; if the microsphere breaks, the slurry entering the interior will form a new solid-state heat transfer path. Therefore, reducing the breakage rate is an important condition for maintaining the thermal insulation performance of the coating. The composite shell also improves the interfacial bonding between the microspheres and the inorganic cementitious phase, making it less likely for the microspheres to separate from the matrix during the curing process. Aerogel provides a nanoscale porous thermal insulation structure, while hollow glass microspheres provide a micrometer-scale closed air cavity. Both restrict heat transfer at different scales, enabling the coating to form a continuous multi-scale thermal insulation structure.
[0017] 3. Modified aerogel and modified hollow glass microspheres differ in density, particle size, and surface properties, making them prone to buoyancy and stratification during wet mixing and the initial setting stage of the cementitious material. This results in uneven distribution of the two types of insulating particles along the coating thickness, hindering their synergistic insulating effect. To address this issue, this invention simultaneously incorporates expanded vermiculite and chopped basalt fibers into the coating. Expanded vermiculite provides large-volume local support and particle confinement in the slurry through its lamellar structure, but lacks stable connections between the lamellars, making it difficult to form a continuous skeleton throughout the slurry when used alone. Chopped basalt fibers can connect different regions, but when used alone, they are prone to local entanglement and are insufficient to provide uniform planar support for low-density insulating particles. When used in combination, expanded vermiculite forms dispersed lamellar support units, while chopped basalt fibers connect adjacent lamellar support units into a cross-scale physical skeleton, allowing both aerogel and hollow glass microspheres to be simultaneously supported by planar structure and constrained by fiber connections. Therefore, in this scheme, expanded vermiculite is responsible for forming the supporting foundation, and short-cut basalt fibers are responsible for maintaining the continuity of the supporting structure. Without either one, it is difficult to form a complete spatially stable skeleton. The combination of the two is a necessary condition for reducing the buoyancy and stratification of the insulation particles and maintaining the uniformity and continuity of the multi-scale heat-insulating structure. Attached Figure Description
[0018] Figure 1 This is a SEM image of the surface of the heat-insulating and cooling coating prepared in Example 5 of the present invention after coating. Detailed Implementation
[0019] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0020] Example 1 A method for preparing an aerogel-modified inorganic-based thermal insulation and cooling coating for deep well tunnels includes the following steps: Step S1: Set D50 to 25 μm and BET specific surface area to 650 m². 2 100 g of hydrophilic SiO2 aerogel was vacuum dried at 105 °C for 4 h, and the initial surface silanol content was measured to be 0.90 mmol / g. The dried aerogel was placed in a closed reactor with low-speed stirring and nitrogen protection, and 4.4 g of hexamethyldisilazane was added. The aerogel was subjected to gas-phase methylation treatment at 90 °C for 3 h. After the reaction was completed, nitrogen was purged at 85 °C for 1.5 h to remove unreacted hexamethyldisilazane and ammonia produced in the reaction. The residual silanol content of the resulting hydrophobic SiO2 aerogel was controlled to be 0.36 mmol / g.
[0021] 2.4 g of 3-aminopropyltriethoxysilane and 3.5 g of 3-glycidoxypropyltrimethoxysilane were added to a mixed solvent consisting of 700 g of anhydrous ethanol and 60 g of deionized water. The apparent pH was adjusted to 4.5 with acetic acid, and the mixture was stirred at 25 °C for 35 min for pre-hydrolysis. 100 g of the partially hydrophobic SiO2 aerogel was added, and the mixture was stirred at 40 °C and 150 r / min for 60 min. Then, 5% (w / w) ammonia was added dropwise to adjust the apparent pH to 8.0, and the reaction was continued at 58 °C for 3 h. After the reaction was completed, the mixture was filtered, washed three times with 300 g of anhydrous ethanol, and vacuum dried at 75 °C and a gauge pressure not exceeding -0.08 MPa for 7 h to obtain organosiloxane interface-modified SiO2 aerogel.
[0022] Step S2: Take 100g of closed-cell hollow glass microspheres with a D50 of 40μm and dry them at 80℃ for 2h. Add 9g of tetraethyl orthosilicate to a mixed medium consisting of 340g of anhydrous ethanol and 18g of deionized water, adjust the pH to 3.8 with acetic acid, and stir at 25℃ for 30min for pre-hydrolysis. Separately, take 1.5g of zirconium propoxide (based on the effective ingredient), mix it with acetylacetone and 60g of anhydrous ethanol for 20min, where the molar ratio of acetylacetone to zirconium is approximately 0.45:1. Add the resulting zirconium precursor solution dropwise to the pre-hydrolyzed tetraethyl orthosilicate solution over 30min, and continue stirring for 30min. Add the dried hollow glass microspheres, stir at 38℃ and 150r / min for 2h, then add 5% (w / w) ammonia water to adjust the pH of the system to 7.5 and continue stirring for 1h. After the reaction was completed, the product was filtered and washed twice with 200g of anhydrous ethanol. It was then dried at 80℃ for 6h. The dried product was then placed in a heat treatment furnace and heated to 300℃ at 2℃ / min. After holding at this temperature for 1h, it was naturally cooled to obtain SiO2-ZrO2 composite shell modified hollow glass microspheres.
[0023] Step S3: Weigh out particles with a size of 70 mesh and a bulk density of 120 kg / m³. 3 9g of expanded vermiculite and 0.7g of short-cut basalt fibers (3mm in length and 12μm in diameter) were added to a ribbon mixer and premixed at 50r / min for 3min to ensure the short-cut basalt fibers were evenly dispersed between the expanded vermiculite layers. Separately, 38g of sulfoaluminate cement, 4.5g of anhydrous calcium sulfate, 15g of metakaolin, 9g of acicular wollastonite, 0.5g of powdered polycarboxylate superplasticizer, 0.23g of hydroxypropyl methylcellulose water-retaining and thickening agent, and 0.35g of cement-based powdered defoamer were weighed and dry-mixed at 60r / min for 4min. Then, the premix of expanded vermiculite and short-cut basalt fibers was added, and mixing continued at 40r / min for 3min to obtain an inorganic skeleton premix.
[0024] Step S4: At 23℃, add 33.6g of deionized water to a low-shear mixer, then add the inorganic skeleton premix obtained in step S3, and stir at a paddle tip speed of 3.0m / s for 3min; add the remaining 8.4g of deionized water and continue stirring for 1min. Weigh 11g of the modified SiO2 aerogel obtained in step S1 and add it to the inorganic slurry in three portions, stirring at a paddle tip speed of 1.2m / s for 1min after each addition. After all the slurry has been added, stop stirring and allow it to stand and wet for 2min. Finally, add 20g of the composite shell modified hollow glass microspheres obtained in step S2 and stir at a low speed of 0.7m / s for 2min. After mixing evenly, the aerogel-modified inorganic-based deep well tunnel heat insulation and cooling coating is obtained.
[0025] Example 2 A method for preparing an aerogel-modified inorganic-based thermal insulation and cooling coating for deep well tunnels includes the following steps: Step S1: Set D50 to 25 μm and BET specific surface area to 650 m². 2 100 g of hydrophilic SiO2 aerogel was vacuum dried at 105 °C for 4 h, and the initial surface silanol content was measured to be 0.90 mmol / g. The dried aerogel was placed in a closed reactor with low-speed stirring and nitrogen protection, and 4.4 g of hexamethyldisilazane was added. The aerogel was subjected to gas-phase methylation treatment at 90 °C for 3 h. After the reaction was completed, nitrogen was purged at 85 °C for 1.5 h to remove unreacted hexamethyldisilazane and ammonia produced in the reaction. The residual silanol content of the resulting hydrophobic SiO2 aerogel was controlled to be 0.36 mmol / g.
[0026] 2.3 g of 3-aminopropyltriethoxysilane and 3.3 g of 3-glycidoxypropyltrimethoxysilane were added to a mixed solvent consisting of 700 g of anhydrous ethanol and 60 g of deionized water. The apparent pH was adjusted to 4.5 with acetic acid, and the mixture was stirred at 25 °C for 35 min for pre-hydrolysis. 100 g of the partially hydrophobic SiO2 aerogel was added, and the mixture was stirred at 40 °C and 150 r / min for 60 min. Then, 5% (w / w) ammonia was added dropwise to adjust the apparent pH to 8.0, and the reaction was continued at 58 °C for 3 h. After the reaction was completed, the mixture was filtered, washed three times with 300 g of anhydrous ethanol, and vacuum dried at 75 °C and a gauge pressure not exceeding -0.08 MPa for 7 h to obtain organosiloxane interface-modified SiO2 aerogel.
[0027] Step S2: Take 100g of closed-cell hollow glass microspheres with a D50 of 40μm and dry them at 80℃ for 2h. Add 7g of tetraethyl orthosilicate to a mixed medium consisting of 340g of anhydrous ethanol and 18g of deionized water, adjust the pH to 3.8 with acetic acid, and stir at 25℃ for 30min for pre-hydrolysis. Separately, take 1.0g of zirconium propoxide (based on the effective ingredient), mix it with acetylacetone and 60g of anhydrous ethanol for 20min, where the molar ratio of acetylacetone to zirconium is approximately 0.35:1. Add the resulting zirconium precursor solution dropwise to the pre-hydrolyzed tetraethyl orthosilicate solution over 30min, and continue stirring for 30min. Add the dried hollow glass microspheres, stir at 38℃ and 150r / min for 2h, then add 5% (w / w) ammonia water to adjust the pH of the system to 7.5 and continue stirring for 1h. After the reaction was completed, the product was filtered and washed twice with 200g of anhydrous ethanol. It was then dried at 80℃ for 6h. The dried product was then placed in a heat treatment furnace and heated to 300℃ at 2℃ / min. After holding at this temperature for 1h, it was naturally cooled to obtain SiO2-ZrO2 composite shell modified hollow glass microspheres.
[0028] Step S3: Weigh out particles with a size of 70 mesh and a bulk density of 120 kg / m³. 3 7g of expanded vermiculite and 0.5g of short-cut basalt fibers (3mm in length and 12μm in diameter) were added to a ribbon mixer and premixed at 50r / min for 3min to ensure the short-cut basalt fibers were evenly dispersed between the expanded vermiculite layers. Separately, 34g of sulfoaluminate cement, 3.5g of anhydrous calcium sulfate, 12g of metakaolin, 7g of acicular wollastonite, 0.35g of powdered polycarboxylate superplasticizer, 0.18g of hydroxypropyl methylcellulose water-retaining and thickening agent, and 0.25g of cement-based powdered defoamer were weighed and dry-mixed at 60r / min for 4min. Then, the premix of expanded vermiculite and short-cut basalt fibers was added, and mixing continued at 40r / min for 3min to obtain an inorganic skeleton premix.
[0029] Step S4: At 23℃, add 33.6g of deionized water to a low-shear mixer, then add the inorganic skeleton premix obtained in step S3, and stir at a paddle tip speed of 3.0m / s for 3min; add the remaining 8.4g of deionized water and continue stirring for 1min. Weigh 9g of the modified SiO2 aerogel obtained in step S1 and add it to the inorganic slurry in three portions, stirring at a paddle tip speed of 1.2m / s for 1min after each addition. After all the slurry is added, stop stirring and let it stand to wet for 2min. Finally, add 16g of the composite shell modified hollow glass microspheres obtained in step S2, and stir at a low speed of 0.7m / s for 2min. After mixing evenly, the aerogel-modified inorganic-based deep well tunnel heat insulation and cooling coating is obtained.
[0030] Example 3 A method for preparing an aerogel-modified inorganic-based thermal insulation and cooling coating for deep well tunnels includes the following steps: Step S1: Set D50 to 25 μm and BET specific surface area to 650 m². 2 100 g of hydrophilic SiO2 aerogel was vacuum dried at 105 °C for 4 h, and the initial surface silanol content was measured to be 0.90 mmol / g. The dried aerogel was placed in a closed reactor with low-speed stirring and nitrogen protection, and 4.4 g of hexamethyldisilazane was added. The aerogel was subjected to gas-phase methylation treatment at 90 °C for 3 h. After the reaction was completed, nitrogen was purged at 85 °C for 1.5 h to remove unreacted hexamethyldisilazane and ammonia produced in the reaction. The residual silanol content of the resulting hydrophobic SiO2 aerogel was controlled to be 0.36 mmol / g.
[0031] 2.35 g of 3-aminopropyltriethoxysilane and 3.4 g of 3-glycidoxypropyltrimethoxysilane were added to a mixed solvent consisting of 700 g of anhydrous ethanol and 60 g of deionized water. The apparent pH was adjusted to 4.5 with acetic acid, and the mixture was stirred at 25 °C for 35 min for pre-hydrolysis. 100 g of the partially hydrophobic SiO2 aerogel was added, and the mixture was stirred at 40 °C and 150 r / min for 60 min. Then, 5% (w / w) ammonia was added dropwise to adjust the apparent pH to 8.0, and the reaction was continued at 58 °C for 3 h. After the reaction was completed, the mixture was filtered, washed three times with 300 g of anhydrous ethanol, and vacuum dried at 75 °C and a gauge pressure not exceeding -0.08 MPa for 7 h to obtain organosiloxane interface-modified SiO2 aerogel.
[0032] Step S2: Take 100g of closed-cell hollow glass microspheres with a D50 of 40μm and dry them at 80℃ for 2h. Add 8g of tetraethyl orthosilicate to a mixed medium consisting of 340g of anhydrous ethanol and 18g of deionized water, adjust the pH to 3.8 with acetic acid, and stir at 25℃ for 30min for pre-hydrolysis. Separately, take 1.2g of zirconium propoxide (based on the effective ingredient), mix it with acetylacetone and 60g of anhydrous ethanol for 20min, where the molar ratio of acetylacetone to zirconium is approximately 0.4:1. Add the resulting zirconium precursor solution dropwise to the pre-hydrolyzed tetraethyl orthosilicate solution over 30min, and continue stirring for 30min. Add the dried hollow glass microspheres, stir at 38℃ and 150r / min for 2h, then add 5% (w / w) ammonia water to adjust the pH of the system to 7.5 and continue stirring for 1h. After the reaction was completed, the product was filtered and washed twice with 200g of anhydrous ethanol. It was then dried at 80℃ for 6h. The dried product was then placed in a heat treatment furnace and heated to 300℃ at 2℃ / min. After holding at this temperature for 1h, it was naturally cooled to obtain SiO2-ZrO2 composite shell modified hollow glass microspheres.
[0033] Step S3: Weigh out particles with a size of 70 mesh and a bulk density of 120 kg / m³. 3 8g of expanded vermiculite and 0.6g of short-cut basalt fibers (3mm in length and 14μm in diameter) were added to a ribbon mixer and premixed at 50r / min for 3min to ensure the short-cut basalt fibers were evenly dispersed between the expanded vermiculite layers. Separately, 36g of sulfoaluminate cement, 4g of anhydrous calcium sulfate, 13g of metakaolin, 8g of acicular wollastonite, 0.45g of powdered polycarboxylate superplasticizer, 0.2g of hydroxypropyl methylcellulose water-retaining and thickening agent, and 0.3g of cement-based powdered defoamer were weighed and dry-mixed at 60r / min for 4min. Then, the premix of expanded vermiculite and short-cut basalt fibers was added, and mixing continued at 40r / min for 3min to obtain an inorganic skeleton premix.
[0034] Step S4: At 23℃, add 33.6g of deionized water to a low-shear mixer, then add the inorganic skeleton premix obtained in step S3, and stir at a paddle tip speed of 3.0m / s for 3min; add the remaining 8.4g of deionized water and continue stirring for 1min. Weigh 10g of the modified SiO2 aerogel obtained in step S1 and add it to the inorganic slurry in three portions, stirring at a paddle tip speed of 1.2m / s for 1min after each addition. After all the slurry is added, stop stirring and let it stand to wet for 2min. Finally, add 18g of the composite shell modified hollow glass microspheres obtained in step S2, and stir at a low speed of 0.7m / s for 2min. After mixing evenly, the aerogel-modified inorganic-based deep well tunnel heat insulation and cooling coating is obtained.
[0035] Example 4 A method for preparing an aerogel-modified inorganic-based thermal insulation and cooling coating for deep well tunnels includes the following steps: Step S1: Set D50 to 25 μm and BET specific surface area to 650 m². 2 100 g of hydrophilic SiO2 aerogel was vacuum dried at 105 °C for 4 h, and the initial surface silanol content was measured to be 0.90 mmol / g. The dried aerogel was placed in a closed reactor with low-speed stirring and nitrogen protection, and 4.4 g of hexamethyldisilazane was added. The aerogel was subjected to gas-phase methylation treatment at 90 °C for 3 h. After the reaction was completed, nitrogen was purged at 85 °C for 1.5 h to remove unreacted hexamethyldisilazane and ammonia produced in the reaction. The residual silanol content of the resulting hydrophobic SiO2 aerogel was controlled to be 0.36 mmol / g.
[0036] 2.5 g of 3-aminopropyltriethoxysilane and 3.6 g of 3-glycidoxypropyltrimethoxysilane were added to a mixed solvent consisting of 700 g of anhydrous ethanol and 60 g of deionized water. The apparent pH was adjusted to 4.5 with acetic acid, and the mixture was stirred at 25 °C for 35 min for pre-hydrolysis. 100 g of the partially hydrophobic SiO2 aerogel was added, and the mixture was stirred at 40 °C and 150 r / min for 60 min. Then, 5% (w / w) ammonia water was added dropwise to adjust the apparent pH to 8.0, and the reaction was continued at 58 °C for 3 h. After the reaction was completed, the mixture was filtered, washed three times with 300 g of anhydrous ethanol, and vacuum dried at 75 °C and a gauge pressure not exceeding -0.08 MPa for 7 h to obtain organosiloxane interface-modified SiO2 aerogel.
[0037] Step S2: Take 100g of closed-cell hollow glass microspheres with a D50 of 55μm and dry them at 80℃ for 2h. Add 10g of tetraethyl orthosilicate to a mixed medium consisting of 340g of anhydrous ethanol and 18g of deionized water, adjust the pH to 4.0 with acetic acid, and stir at 30℃ for 40min for pre-hydrolysis. Separately, take 1.6g of zirconium propoxide (based on the effective ingredient), mix it with acetylacetone and 60g of anhydrous ethanol for 20min, where the molar ratio of acetylacetone to zirconium is approximately 0.5:1. Add the resulting zirconium precursor solution dropwise to the pre-hydrolyzed tetraethyl orthosilicate solution over 30min, and continue stirring for 30min. Add the dried hollow glass microspheres, stir at 40℃ and 150r / min for 2.5h, then add 5% (w / w) ammonia water dropwise to adjust the pH of the system to 7.8 and continue stirring for 1.5h. After the reaction was completed, the product was filtered and washed twice with 200g of anhydrous ethanol. It was then dried at 80℃ for 6h. The dried product was then placed in a heat treatment furnace and heated to 320℃ at 3℃ / min. After holding at this temperature for 1.5h, it was naturally cooled to obtain SiO2-ZrO2 composite shell modified hollow glass microspheres.
[0038] Step S3: Weigh out particles with a size of 80 mesh and a bulk density of 150 kg / m³. 3 10g of expanded vermiculite and 0.8g of short-cut basalt fibers (4mm in length and 17μm in diameter) were added to a ribbon mixer and premixed at 50r / min for 3min to ensure the short-cut basalt fibers were evenly dispersed between the expanded vermiculite layers. Separately, 40g of sulfoaluminate cement, 5g of anhydrous calcium sulfate, 16g of metakaolin, 10g of acicular wollastonite, 0.6g of powdered polycarboxylate superplasticizer, 0.25g of hydroxypropyl methylcellulose water-retaining and thickening agent, and 0.4g of cement-based powdered defoamer were weighed and dry-mixed at 60r / min for 4min. Then, the premix of expanded vermiculite and short-cut basalt fibers was added, and mixing continued at 40r / min for 3min to obtain an inorganic skeleton premix.
[0039] Step S4: At 23℃, add 33.6g of deionized water to a low-shear mixer, then add the inorganic skeleton premix obtained in step S3, and stir at a paddle tip speed of 3.0m / s for 3min; add the remaining 8.4g of deionized water and continue stirring for 1min. Weigh 12g of the modified SiO2 aerogel obtained in step S1 and add it to the inorganic slurry in three portions, stirring at a paddle tip speed of 1.2m / s for 1min after each addition. After all the slurry is added, stop stirring and let it stand to wet for 2min. Finally, add 21g of the composite shell modified hollow glass microspheres obtained in step S2, and stir at a low speed of 0.7m / s for 2min. After mixing evenly, the aerogel-modified inorganic-based deep well tunnel heat insulation and cooling coating is obtained.
[0040] Example 5 A method for preparing an aerogel-modified inorganic-based thermal insulation and cooling coating for deep well tunnels includes the following steps: Step S1: Set D50 to 25 μm and BET specific surface area to 650 m². 2 100 g of hydrophilic SiO2 aerogel was vacuum dried at 105 °C for 4 h, and the initial surface silanol content was measured to be 0.90 mmol / g. The dried aerogel was placed in a closed reactor with low-speed stirring and nitrogen protection, and 4.4 g of hexamethyldisilazane was added. The aerogel was subjected to gas-phase methylation treatment at 90 °C for 3 h. After the reaction was completed, nitrogen was purged at 85 °C for 1.5 h to remove unreacted hexamethyldisilazane and ammonia produced in the reaction. The residual silanol content of the resulting hydrophobic SiO2 aerogel was controlled to be 0.36 mmol / g.
[0041] 2.2 g of 3-aminopropyltriethoxysilane and 3.2 g of 3-glycidoxypropyltrimethoxysilane were added to a mixed solvent consisting of 700 g of anhydrous ethanol and 60 g of deionized water. The apparent pH was adjusted to 4.5 with acetic acid, and the mixture was stirred at 25 °C for 35 min for pre-hydrolysis. 100 g of the partially hydrophobic SiO2 aerogel was added, and the mixture was stirred at 40 °C and 150 r / min for 60 min. Then, 5% (w / w) ammonia was added dropwise to adjust the apparent pH to 8.0, and the reaction was continued at 58 °C for 3 h. After the reaction was completed, the mixture was filtered, washed three times with 300 g of anhydrous ethanol, and vacuum dried at 75 °C and a gauge pressure not exceeding -0.08 MPa for 7 h to obtain organosiloxane interface-modified SiO2 aerogel.
[0042] Step S2: Take 100g of closed-cell hollow glass microspheres with a D50 of 25μm and dry them at 80℃ for 2h. Add 6g of tetraethyl orthosilicate to a mixed medium consisting of 340g of anhydrous ethanol and 18g of deionized water, adjust the pH to 3.5 with acetic acid, and stir at 20℃ for 20min for pre-hydrolysis. Separately, take 0.9g of zirconium propoxide (based on the effective ingredient), mix it with acetylacetone and 60g of anhydrous ethanol for 20min, where the molar ratio of acetylacetone to zirconium is approximately 0.3:1. Add the resulting zirconium precursor solution dropwise to the pre-hydrolyzed tetraethyl orthosilicate solution over 30min, and continue stirring for 30min. Add the dried hollow glass microspheres, stir at 35℃ and 150r / min for 1.5h, then add 5% (w / w) ammonia water dropwise to adjust the pH of the system to 7.2 and continue stirring for 0.5h. After the reaction was completed, the product was filtered and washed twice with 200g of anhydrous ethanol. It was then dried at 80℃ for 6h. The dried product was then placed in a heat treatment furnace and heated to 280℃ at 1℃ / min. After holding at this temperature for 0.5h, it was naturally cooled to obtain SiO2-ZrO2 composite shell modified hollow glass microspheres.
[0043] Step S3: Weigh out particles with a size of 60 mesh and a bulk density of 80 kg / m³. 3 6g of expanded vermiculite and 0.4g of short-cut basalt fibers (2mm in length and 9μm in diameter) were added to a ribbon mixer and premixed at 50r / min for 3min to ensure the short-cut basalt fibers were evenly dispersed between the expanded vermiculite layers. Separately, 32g of sulfoaluminate cement, 3g of anhydrous calcium sulfate, 10g of metakaolin, 6g of acicular wollastonite, 0.3g of powdered polycarboxylate superplasticizer, 0.15g of hydroxypropyl methylcellulose water-retaining and thickening agent, and 0.2g of cement-based powdered defoamer were weighed and dry-mixed at 60r / min for 4min. Then, the premix of expanded vermiculite and short-cut basalt fibers was added, and mixing continued at 40r / min for 3min to obtain an inorganic skeleton premix.
[0044] Step S4: At 23℃, add 33.6g of deionized water to a low-shear mixer, then add the inorganic skeleton premix obtained in step S3, and stir at a paddle tip speed of 3.0m / s for 3min; add the remaining 8.4g of deionized water and continue stirring for 1min. Weigh 8g of the modified SiO2 aerogel obtained in step S1 and add it to the inorganic slurry in three portions, stirring at a paddle tip speed of 1.2m / s for 1min after each addition. After all the slurry is added, stop stirring and let it stand to wet for 2min. Finally, add 15g of the composite shell modified hollow glass microspheres obtained in step S2, and stir at a low speed of 0.7m / s for 2min. After mixing evenly, the aerogel-modified inorganic-based deep well tunnel heat insulation and cooling coating is obtained.
[0045] Comparative Example 1: Compared with Example 5, step S1 did not use 3-aminopropyltriethoxysilane and 3-glycidoxypropyltrimethoxysilane for interface modification, and step S4 directly added 8g of partially hydrophobic SiO2 aerogel that had been incompletely methylated with hexamethyldisilazane. The remaining raw materials, amounts and preparation processes were the same as in Example 5.
[0046] Comparative Example 2: Compared with Example 5, step S2 did not use tetraethyl orthosilicate and zirconium propoxide coordinated with acetylacetone to coat the hollow glass microspheres, and step S4 directly added 15g of hollow glass microspheres of the same specification without composite shell modification. The remaining raw materials, dosages and preparation processes were the same as in Example 5.
[0047] Comparative Example 3: Compared with Example 5, the modified SiO2 aerogel obtained in step S1 was replaced by an equal mass of partially hydrophobic SiO2 aerogel that was not modified by the organosiloxane interface, and the composite shell modified hollow glass microspheres obtained in step S2 were replaced by an equal mass of uncoated hollow glass microspheres of the same specification. The remaining raw materials, dosages and preparation processes were the same as in Example 5.
[0048] Comparative Example 4: Compared with Example 5, step S3 did not include 6g of expanded vermiculite, but was made up with 6g of acicular wollastonite and other materials. The amount of chopped basalt fiber remained unchanged at 0.4g. All other raw materials, amounts and preparation processes were the same as in Example 5.
[0049] Comparative Example 5: Compared with Example 5, step S3 did not include 0.4g of short-cut basalt fiber, but was made up with 0.4g of needle-shaped wollastonite and other materials. The amount of expanded vermiculite remained unchanged at 6g. All other raw materials, amounts and preparation processes were the same as in Example 5.
[0050] Comparative Example 6: Compared with Example 5, step S3 omitted 6g of expanded vermiculite and 0.4g of short-cut basalt fiber, and made up the difference with 6.4g of acicular wollastonite, etc. The remaining raw materials, amounts and preparation processes were the same as in Example 5.
[0051] Performance testing I. Testing Methods Specimen preparation: The coatings obtained in Examples 1-5 and Comparative Examples 1-6 were respectively placed into the corresponding molds and leveled with a scraper to avoid vibration that could cause the aerogel and hollow glass microspheres to float or break. The specimens were cured at a temperature of 23±2℃ and a relative humidity of 90±5% for 7 days, and then cured for another 28 days at a temperature of 23±2℃ and a relative humidity of 50±5%. Unless otherwise specified, three parallel specimens were prepared for each performance test, and the results in the table are the arithmetic mean.
[0052] 1. Dry thermal conductivity test: According to GB / T 10294-2008, a 300mm×300mm×20mm plate specimen was prepared, cured for 28 days, dried to constant weight at 60±2℃, and cooled to room temperature in a desiccator; the thermal conductivity was determined by the protective hot plate method, the average test temperature was 25±1℃, the temperature difference between the hot and cold surfaces was 20±2℃, and the results were recorded after the heat flow and the temperature on both sides reached a stable state. The unit is W / (m·K).
[0053] 2. Thermal conductivity test after high humidity treatment: Plate-shaped specimens of the same specifications as the dry-state thermal conductivity specimens were placed in a constant temperature and humidity chamber at 35±2℃ and 95±3% relative humidity for 14 days. Immediately after removal, they were sealed with a polyethylene film no thicker than 0.03mm to prevent water loss during the test. The thermal conductivity was measured under the same temperature conditions as the dry-state thermal conductivity specimens, and the film thermal resistance was deducted. The thermal conductivity growth rate was calculated as "(thermal conductivity after high humidity treatment - dry-state thermal conductivity) / dry-state thermal conductivity × 100%".
[0054] 3.24h mass water absorption rate test: Dry the 100mm×100mm×20mm specimen at 60±2℃ to constant weight and weigh it to obtain the dried mass m0. Then, completely immerse the specimen in deionized water at 20±2℃, maintaining a distance of not less than 10mm between specimens and between the specimen and the container wall. After soaking for 24h, take it out, wipe off the surface water with a damp cloth and weigh it within 1min to obtain the mass m1. Calculate the 24h mass water absorption rate according to (m1-m0) / m0×100%.
[0055] 4. Tensile bond strength test. The coating was applied twice to the pre-wetted and dry concrete substrate surface, with a total coating thickness of 10±0.5mm. After curing for 28 days, the coating was cut into independent test areas of 40mm×40mm. Pull-out heads were bonded with epoxy structural adhesive. After the adhesive was fully cured, the pull-out heads were stretched vertically at a loading speed of 5±1mm / min until failure. The tensile bond strength was calculated by dividing the maximum tensile force by the test area, and the unit was MPa.
[0056] 5. Compressive strength test. A cubic specimen with dimensions of 70.7mm × 70.7mm × 70.7mm was prepared. After curing for 28 days, a pressure testing machine was used to continuously and uniformly load the specimen at a rate controlled between 0.05 and 0.10 MPa / s until failure. The compressive strength was calculated by dividing the maximum failure load by the bearing area, expressed in MPa, and the main failure modes were recorded.
[0057] 6. Simulated Hot Wall Insulation and Cooling Test: Concrete slabs of the same batch (300mm×300mm×30mm) were used to simulate the surrounding rock of the tunnel. A 10±0.3mm thick coating was applied to one side of the slab. After curing for 28 days, the uncoated side of the concrete slab was bonded to a constant-temperature hot plate, maintained at 50.0±0.2℃. The coating surface was exposed to an environment of 25±1℃ without forced airflow, and the specimen was insulated around its perimeter. Steady-state conditions were defined as the temperature change at the center of the coating not exceeding 0.2℃ after three consecutive measurements at 10-minute intervals. Under the same conditions, the steady-state surface temperature of the uncoated concrete slab was 47.2℃. The insulation and cooling value was calculated as "47.2℃ - steady-state surface temperature of the coating".
[0058] Table 1:
[0059] Compared with Comparative Example 1, Example 5 showed a decrease in dry thermal conductivity of approximately 13.0%, a decrease in thermal conductivity of approximately 20.4% after high humidity treatment, a decrease in 24-hour water absorption rate of approximately 31.5%, and an increase in tensile bond strength of approximately 37.5%. This trend indicates that although the partially hydrophobic aerogel without interface layer modification still possesses a nanoporous thermal insulation structure, it is prone to insufficient wetting and local aggregation in aqueous inorganic slurries, failing to form a uniform thermal insulation region and easily generating interfacial pores. After regulation with aminosilane and epoxysilane, the aerogel retains some hydrophobicity while achieving better slurry compatibility, thus improving both thermal insulation stability and interfacial bonding performance under high humidity conditions.
[0060] Compared to Comparative Example 2, Example 5 showed a decrease in dry thermal conductivity of approximately 16.4%, an increase in 28-day compressive strength of approximately 22.9%, and an increase in thermal insulation temperature reduction from 9.7℃ to 11.1℃. This change is mainly consistent with the protective effect of the composite shell on the hollow glass microspheres: uncoated microspheres are more prone to breakage during mixing, loading, and molding, and the slurry entering the interior of broken microspheres increases the solid-phase heat transfer path; after forming the SiO2-ZrO2 composite shell, the retention rate of the microsphere's closed air cavity is improved, while the interface defects between the microspheres and the inorganic cementitious phase are reduced. In Comparative Example 3, after simultaneously eliminating the two types of thermal insulation filler modifications, the decrease in various thermal insulation and moisture resistance indicators was the most significant, indicating that the two types of interface control have a synergistic effect at different scales.
[0061] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the essence and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing an aerogel-modified inorganic-based thermal insulation and cooling coating for deep well tunnels, characterized in that, Includes the following steps: S1. A partially hydrophobic SiO2 aerogel with both hydrophobic groups and reactive silanol groups on its surface is contacted with aminosilane and epoxysilane in an alcohol-water medium, so that the aminosilane and epoxysilane are hydrolyzed and condensed on the surface of the aerogel to obtain an organosiloxane interface layer modified SiO2 aerogel. S2. Hydrolyze and condense the hydrolyzable silicon source and the hydrolyzable zirconium source on the surface of the hollow glass microspheres, and then solidify them to form a SiO2-ZrO2 composite shell, thus obtaining composite shell modified hollow glass microspheres. S3. Premix expanded vermiculite with short-cut basalt fibers, and then mix it with inorganic powder and additives containing sulfoaluminate cement, calcium sulfate, metakaolin, acicular wollastonite, etc. to obtain inorganic skeleton premix. The expanded vermiculite has a particle size of 60-100 mesh and a bulk density of 80-150 kg / m³. 3 The chopped basalt fibers have a length of 2–4 mm and a diameter of 9–17 μm; The additives include polycarboxylate superplasticizer, hydroxypropyl methylcellulose water-retaining and thickening agent, and powder defoamer; S4. The inorganic skeleton premix is mixed with water to form an inorganic slurry. Modified SiO2 aerogel and composite shell modified hollow glass microspheres are added to the inorganic slurry in sequence. After mixing evenly, the heat insulation and cooling coating is obtained. The mass fraction ratio of the components in the heat insulation and cooling coating is as follows: The composition includes 32-40 parts of sulfoaluminate cement, 3-5 parts of calcium sulfate, 10-16 parts of metakaolin, 8-12 parts of modified SiO2 aerogel, 15-21 parts of composite shell modified hollow glass microspheres, 6-10 parts of expanded vermiculite, 0.4-0.8 parts of short-cut basalt fiber, 6-10 parts of acicular wollastonite, 0.3-0.6 parts of polycarboxylate superplasticizer, 0.15-0.25 parts of hydroxypropyl methylcellulose water-retaining and thickening agent, and 0.2-0.4 parts of powder defoamer.
2. The preparation method of the aerogel-modified inorganic-based deep well tunnel heat insulation and cooling coating according to claim 1, characterized in that, In step S1, the partially hydrophobic SiO2 aerogel is a SiO2 aerogel that has undergone incomplete methylation treatment with hexamethyldisilazane.
3. The preparation method of the aerogel-modified inorganic-based deep well tunnel heat insulation and cooling coating according to claim 1, characterized in that, In step S1, the aminosilane is 3-aminopropyltriethoxysilane, and the epoxysilane is 3-glycidoxypropyltrimethoxysilane; Based on 100 parts by weight of partially hydrophobic SiO2 aerogel, the amount of 3-aminopropyltriethoxysilane is 2.2 to 2.5 parts, and the amount of 3-glycidoxypropyltrimethoxysilane is 3.2 to 3.6 parts.
4. The preparation method of the aerogel-modified inorganic-based deep well tunnel heat insulation and cooling coating according to claim 1, characterized in that, In step S2, the D50 of the hollow glass microspheres is 25-55 μm; the hydrolyzable silicon source is tetraethyl orthosilicate; the hydrolyzable zirconium source is zirconium propoxide; and the zirconium propoxide is coordinated with acetylacetone.
5. The preparation method of an aerogel-modified inorganic-based deep well tunnel thermal insulation and cooling coating according to claim 1, characterized in that, Step S2 includes: Based on 100 parts by weight of hollow glass microspheres, 6-10 parts of tetraethyl orthosilicate were added to an alcohol-water medium and pre-hydrolyzed for 20-40 min at pH 3.5-4.0 and 20-30℃. 0.9 to 1.6 parts of zirconium propoxide based on the effective ingredient were premixed with acetylacetone to make the molar ratio of acetylacetone to zirconium (0.3 to 0.5):1, and then added to the pre-hydrolyzed tetraethyl orthosilicate solution. Add hollow glass microspheres and stir at 35–40°C for 1.5–2.5 h. Adjust the pH of the system to 7.2–7.8 and continue stirring for 0.5–1.5 h. Then filter, wash and dry.
6. The preparation method of an aerogel-modified inorganic-based deep well tunnel heat insulation and cooling coating according to claim 5, characterized in that, The dried hollow glass microspheres were heated to 280-320℃ at a heating rate of 1-3℃ / min and held at that temperature for 0.5-1.5h to solidify the SiO2-ZrO2 composite shell.
7. An aerogel-modified inorganic-based thermal insulation and cooling coating for deep well tunnels, characterized in that, It is prepared by the method described in any one of claims 1 to 6 above.
Citation Information
Patent Citations
Aerogel-containing waterborne thermal-insulation coating and preparation method thereof
CN107266997A
Deep well high-temperature roadway high-strength heat-insulation supporting structure and construction method
CN113958344A